The Use of Enrofloxacin Antibiotic as a Veterinary Drug and Its Residual Hazards on Public Health - Prima Mei Widiyanti; Mirnawati Bachrum Sudarwanto; Etih Sudarnika; raphaella widiastuti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
The livestock sector can improve the community's economy and has a role in fulfilling food needs, especially animal protein. One of the problems in the livestock sector is the presence of infectious diseases that consequently need treatment using veterinary drugs. This paper describes the use of enrofloxacin antibiotics as veterinary drug and their residual hazards on public health. Enrofloxacin is an antibiotic from the family of fluoroquinolones (second generation of quinolone). Enrofloxacin is a broad-spectrum antibiotic that is effective to kill Gram positive and negative bacteria, so it was used for the treatment of various diseases in animals. Pharmacokinetically, enrofloxacin will be metabolized into ciprofloxacin and other metabolites. The improper use of enrofloxacin antibiotics caused residues in food products of animal origin, microbial resistance and toxicity, therefore the use of enrofloxacin needs to be monitored and evaluated for the sake of animal health and society.